PD-L1 on Circulating Tumor Cells Indicates Poor Prognosis in Breast Cancer - Xue-fei Wang; Guo-chao Zhang; Sha-fei Wu; Jia-xin Li; Qiang Sun (IMR Press, 2022)
Background: In breast cancer, research concerning programmed death-ligand 1 (PD-L1) on circulating tumor cells (CTCs) is limited. Besides, the best cell type for determining the prognostic and predictive values of PD-L1 has not been established. This study investigated associations between PD-L1 on tumor cells (TCs), CTCs, and tumor-infiltrating immune cells (TIICs), respectively, and prognosis and clinicopathological features in breast cancer. Methods: Twenty patients with breast cancer were recruited; one was excluded for confirmed lymphoma. The PD-L1 on TCs and TIICs was determined via immunohistochemistry; PD-L1 mRNA expression on CTCs was analyzed. The chi-squared test and Kaplan-Meier and Cox proportional hazards model analyses were applied. Results: The median follow-up time was 60 months. Of the 19 patients, 14 had >1 CTC/10 mL peripheral blood. Among these, each had ≥1 CTC showing PD-L1. At baseline, there was no difference between groups with or without metastasis regarding CTCs and PD-L1 expression. Patients with high PD-L1 levels on CTCs had poor overall survival (p = 0.034). In the multivariate analysis, PD-L1 levels on CTCs and T stage were independent prognostic factors (p = 0.029, 0.010, respectively). Conclusions: High levels of PD-L1 on CTCs may prognose shorter overall survival in breast cancer.